Analisis Kesediaan Membayar (Willingness to Pay) Konsumen Terhadap Pembelian Buah Impor di Pasar Swalayan Kota Semarang - Pratomo, Muhammad Daffa; Mukson, Mukson; Roessali, Wiludjeng (Universitas Galuh, 2026)
This research aims to analyze consumers' Willingness to Pay (WTP) for imported fruits (Fuji apple, red grape, and pear) and to analyze the influence of consumer characteristics on the WTP value in the supermarkets of Semarang City. This study employed a survey method with a quota sampling technique on 150 respondents who are consumers of imported fruits in three selected supermarkets in Semarang City. Data analysis to determine the average WTP value used the Contingent Valuation Method (CVM), while the influence of consumer characteristics—including age, education, income, health consciousness, and expenditure on imported fruits—was analyzed using logistic regression. The results showed that the majority of consumers were willing to pay more, with the highest average WTP increase for red grapes (13.30%), followed by Fuji apples (12.75%), and pears (10.50%). The logistic regression analysis indicated that the factors influencing WTP differed for each fruit. The WTP for Fuji apples was positively influenced by expenditure on imported fruits. The WTP for red grapes was negatively influenced by age and positively by health consciousness. Meanwhile, the WTP for pears was negatifvely influenced by age. The variables of education and income were not found to have a partially significant influence on the WTP for any of the three fruit types.